Female Perspectives sebagai Representasi Karya Foto Mahasiswa Perempuan - Suratni, Suratni; Widiastuti, Ni Made; Suwarni, Wahyu; Amelia, Diah (Rekam, 2024)
ABSTRACT In 2024, the Photography Study Program at Politeknik Negeri Media Kreatif will be 14 years old. This study program has produced hundreds of skilled photographer alumni who work in the creative industry. Every year, students hold a number of exhibitions to actualize their works. One of them is an exhibition of photos by female students called the Women's Exhibition. This article aims to explain how a photobook becomes a medium of representation of female student photography. The references used are several previous studies with the same focus on discussion. The method used is qualitative descriptive, with a photo curation technique from the results of the Women's Exhibition. Various interpretations on women are embodied in dozens of photo works which are then compiled into a photobook entitled Female Perspectives, which has six categories, namely (1) female beauty perspectives, (2) female food perspectives, (3) female profession perspectives, (4) female traveling perspectives, (5) female sport and healthy perspectives, and (6) female lifestyle perspectives. With the publication of this photobook, female students can represent their opinions on today's women in the form of a photobook, so that they can get their artistic value and economic value.Keywords: women's perspectives, photobook, representation, student work ABSTRAKTahun 2024, Prodi Fotografi di Politeknik Negeri Media Kreatif genap berusia 14 tahun. Prodi ini telah mencetak ratusan alumni fotografer terampil yang berkarya di bidang industri kreatif. Setiap tahunnya, mahasiswa menggelar sejumlah pameran untuk mengaktualisasikan karya-karya mereka. Salah satunya adalah pameran foto karya mahasiswa perempuan yang diberi nama Pameran Perempuan. Artikel ini bertujuan untuk menjelaskan bagaimana photobook menjadi media representasi karya foto mahasiswa perempuan. Referensi yang digunakan adalah beberapa penelitian terdahulu dengan fokus pembahasan yang sama. Metode yang digunakan adalah kualitatif deskriptif, dengan teknik kurasi foto dari hasil Pameran Perempuan. Berbagai pandangan tentang perempuan diwujudkan dalam puluhan karya foto yang kemudian disusun menjadi sebuah photobook yang berjudul Female Perspectives, yang memiliki enam kategori, yaitu (1) female beauty perspectives, (2) female food perspectives, (3) female profession perspectives, (4) female travelling perspectives, (5) female sport and healthy perspectives, and (6) female lifestyle perspectives. Dengan diterbitkannya photobook ini, mahasiswa perempuan dapat merepresentasikan pandangan mereka tentang perempuan masa kini dalam bentuk photobook, sehingga didapat nilai seni dan nilai ekonomisnya. Kata kunci: pandangan perempuan, photobook, representasi, karya mahasiswa